Letter to Jane Tolmach from Walter M. Ingalls - Walter M. Ingalls:::::: (1976)
In a May 13, 1976 letter marked "Personal and Confidential," Assemblyman Walter M. Ingalls informed Jane Tolmach that he endorsed her candidacy for the State Assembly. He described her as one of the most able candidates running in any Assembly race in California and expressed his anticipation of serving with her in the Legislature. As a member of the Democratic Caucus Campaign Committee, Ingalls stated that he would advocate for her candidacy among fellow Democratic legislators. He hoped his discussions would provide meaningful assistance to her campaign.